Cell Phones and Rural Labor Markets: Evidence from South Africa - Stefan Klonner; Patrick J. Nolen (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
We study the labor market effects of the roll-out of mobile phone coverage in rural South Africa. We address identification issues which arise from the fact that network roll-out cannot be viewed as an exogenous process to local economic development. We combine spatially coded data from South Africa's leading network provider with annual labor force surveys. We use terrain properties to construct an instrumental variable that allows us to identify the causal effect of network coverage on economic outcomes under plausible assumptions. We find substantial effects of network roll-out on labor market outcomes with remarkable gender-specific differences. Employment increases by 15 percentage points when a locality receives network coverage. A gender- differentiated analysis shows that most of this effect is due to increased employment by women, in particular those who are not burdened with large child care responsibilities at their homes. All of the employment gains accrue in wage employed occupations. Agricultural employment decreases substantially, especially among males.
Keywords: O15; O22; J22; 330; Mobile Phones; Economic Development; Project Evaluation